RECONSTRUCTING SOCIAL CONTEXT FROM FAITH AND THE SOCIO-POLITICAL PARTICIPATION. BALANCE IN BASIC ECCLESIAL COMMUNITY IN NAYARIT, MÉXICO - Orozco Espinosa, Pedro (2016)
This article reconstructs the experience of social organization CEB in Nayarit, duringthe decade of the 80’s and 90’s of last century. In particular, the shooting settings beemphasized as a catalyst and enabler for various actions that took place in a new socialtissue in the body. It is also intended to make a brief overview to explain not only theirrelative success, but its decline in the reconstruction of the social fabric in these places.